Different Topologies and Control Techniques of Compressed Air Energy storage system: A Literature Survey - Rama Rao Bomma, Dr J. Jayakumar, Dr. Shanty chacko (International Journal of Advanced Science and Technology, 2020)
Now a days, maximum developed and developing nations are preferred renewable based power generation for environment friendly sustainable future. Renewable based power generation is increases all-around, different measures like, (i) energy management strategies implementation (ii) demand side management (iii)novel power converters development (iv) Further, modernizing the grid will help power sector to meet different challenges of handling energy requirements as well as the energy is increased from renewable sources while maintaining a electricity release system. Energy storage is a new technology. It is considered aeventual solution in developing smart grid with distributed renewable power generation. Different types of storage technologies are there. Among them, CAES system is more acceptable for more facility storage for grid combination. When CAES system is compared with pumped hydro storage system, the overall roundtrip efficiency is low, in large scale renewable power generation. This challenges the application of the CAES system for renewable energy based power plant. Considering the above challenge, major objective of the small scale CAES system is to increase the overall roundtrip efficiency. The suggested system is designed and constructed for power generation of small scale residential application. Specially, from the thermodynamic study, an interesting idea was also generated.